The introduction of Boran cattle into an ECF (East Coast fever) endemic area - Stobbs, T.H. (1966)
An investigation was made in 1958 to find out if Boran cattle (introduced from Kenya) could be adapted to East Cost Fever (E.C.F.) endemic area of Uganda. A serial artificial immunization trial was made to improve resistance of Boran cattle to E.C.F. either by feeding Aurofac at the rate of 1 oz. per 40 lb liveweight or by matching Boran bulls to local small East African zebu cattle to use their progeny. The overall mortality rate among Boran was 36.4%. Calf mortality recorded from 93 Boran, 74 local zebu crosses with Boran and 231 local zebu showed 77 percent for Boran, 43 percent for Boran crosses and 23 per cent for local zebu. Boran calves weighed on average 401 lb at 12 months, some 57% heavier than Serere Zebu contemporaries. The average mature weight of Boran cows was 884 lb. The mean age at first calving and calving interval were 40±7.2 and 391±5.3 days, respectively. Boran calves not only showed a high mortality but also suffered severe checks in growth. Growth of Boran up to 18 months was approximately 15% faster than zebu contemporaries and Boran crosses were 20% faster growing. It is concluded that the most promising animals are the Boran crosses due to their lower mortality and their good growth.